The prisoner of heaven : a novel - Ruiz Zafón, Carlos, 1964-2020- (Harper, 2012)
In 1957 Barcelona, Daniel Semper and his close friend Fermin Romero de Torres find their lives violently disrupted by the arrival of a mysterious stranger who threatens to divulge a terrible secret that has been buried for two decades in the city's dark past.